THE PRINCIPLES OF TAXES ADMINISTRATION - VIOREL ROŞ (Challenges of the Knowledge Society)
In the management of taxes and contributions are involved three categories of professionals: government officials, economists and lawyers. Somehow or another, everyone involved decide on a significant part of the taxpayers’ income and wealth who constitute the state’s budget revenues. Therefore, the basic rules of tax administration should be known by everyone, including the taxpayers. And they must be applied uniformly. This requires their knowledge.